ChemInform Abstract: Efficient Synthesis of Novel Spiro‐Furo‐Pyrido‐Pyrimidine‐Indolines by Manganese Ferrite Nanoparticles as a Highly Active Magnetically Reusable Nanocatalyst in Water. Issue 18 (17th April 2014) - Naeimi, Hossein; Rashid, Zahra; Zarnani, Amir Hassan; Ghahremanzadeh, Ramin
Abstract The manganese ferrite nanoparticles can be easily separated using an external magnet and retain their catalytic activity for at least five repeated uses.